Trade and sustainable development : spatial distribution of trade policies impacts on agriculture - Ludeña, Carlos [et al] (UN ECLAC SantiagoCL, 2009)
Maps crop distribution at the spatial level by type of producer according to a harmonised product classification. Distributes the economic impacts of trade liberalisation using a general equilibrium model, taking into consideration incomplete international price transmission into domestic markets (rural and urban). Identifies at the sub-national level a subsidy strategy tailored for producer type and crop, that could mitigate possible negative impacts from trade liberalisation.